PENGELOLAAN KOMUNIKASI ORGANISASI DALAM MEWUJUDKAN CITRA SEKOLAH ADIWIYATA - Subar Subar (Universitas Mercu Buana, 2018)
Adiwiyata school must physically look green, beautiful, clean, neat, and bring a sense of security and comfort. SMA Negeri 5 Tangerang which initially has environmental problems is now a school adiwiyata. This incident is interesting and needs to be researched. Qualitative research paradigms with case study method, describe the management of organizational communication that is sought by the management of SMA Negeri 5 Tangerang in building the image of adiwiyata school. The Management Theory is the basic reference for dissecting this research. Communication management begins with planning, compiling tatatertib and rules, establishing organizing committees, mapping target audiences addressing messages, constructing messages verbally or in writing. Organizing, moving all communication components by enabling audiences to perform their roles. Actuating encourages and creates conducive conditions in the form of direction to students, appeals to canteen officers and provides flexibility of work to janitor. The rewards and the threat of punishment are also one of the actuating acts performed. Controlling to know the process and the results achieved have been in accordance with the standards or not. Daily cleaning checks by the committee, reprimands to violators of the rules until the monitoring through CCTV is a control effort undertaken. The results of this program have been achieved, as evidenced by the recognition of adiwiyata school from the Ministry of Environment.Keywords: Management, Communication, Organization